Excessive Internet Use and its association with negative experiences: Quasi-validation of a short scale in 25 European countries. (December 2015) - Škařupová, Kateřina; Ólafsson, Kjartan; Blinka, Lukas
Highlights: The EIU scale is suitable short tool for use in large epidemiological surveys. The EIU score of 2.6 doubles the probability of behavioral and psychological problems. In adolescence, certain levels of EIU may rather be a symptom than primary disorder. Abstract: Prevalence data on Internet addiction in Europe are rather scarce due to the lack of agreement on the definition and measurement of the concept. We define Excessive Internet Use (EIU) as such use of online applications that puts the user at risk of adverse consequences. In this paper, we present a cross-country quasi-validation of the five-item Excessive Internet Use scale that is suitable for use in general population surveys. We worked with EU Kids Online II data for children aged 11–16 in 25 European countries and used a set of regression models to assess the probabilities of various negative consequences for each EIU score. A consistent pattern was identified across Europe when controlling for country differences, suggesting good psychometric properties of the scale. Moreover, our results indicate that EIU in children may be a symptom of broader behavioral difficulties rather than a condition, per se.